Electrical, mechanical and thermal properties of thick film resistors on dielectrics - Jakubowska, Małgorzata; Pitt, Keith (Видавництво Національного університету “Львівська політехніка”, 2005)
Описано останні дослідження в області сумісності товстоплівкових та резистивних комбінацій. Розглянуті причини реакції між матеріалами та подальші зміни в електричних параметрах. Новорозроблені серії резисторів на основі оксиду рутенію демонструють значно кращу електричну і механічну сумісність, ніж старі комбінації. Термографічне картографування і комп’ютерне моделювання розподілу теплових полів навколо нагрітого резистора демонструють значне зростання на нижньому провідному шарі.

This paper examines recent developments in the fabrication of compatible thick film dielectric and resistor combinations. It discusses the causes of reactions between materials and the consequent electrical changes. Results are presented showing that the newly developed ruthenium oxide based resistor series tested here has significantly better electrical and mechanical compatibility than older combinations. Piezoelectric studies show that Gauge Factors, (G.F.), of this series are significantly higher than found in earlier materials on both alumina and dielectric. Thermographic mapping and computer simulation of temperature distribution around heated resistors on alumina and on dielectric on alumina both show a significant rise on the lower conductivity layer.